2010
DOI: 10.2119/molmed.2010.00117
|View full text |Cite
|
Sign up to set email alerts
|

Liver Regeneration Associated Protein (ALR) Exhibits Antimetastatic Potential in Hepatocellular Carcinoma

Abstract: Augmenter of liver regeneration (ALR), which is critically important in liver regeneration and hepatocyte proliferation, is highly expressed in cirrhotic livers and hepatocellular carcinomas (HCC). In the current study, the functional role of ALR in hepatocancerogenesis was analyzed in more detail. HepG2 cells, in which the cytosolic 15 kDa ALR isoform was reexpressed stably, (HepG2-ALR) were used in migration and invasion assays using modified Boyden chambers. Epithelial-mesenchymal transition (EMT) markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…These findings seem contradictory, however, evidence suggests that overexpression of sfALR in cancerous HepG2 cells leads to a reduced invasiveness and cell migration. There is still increased cell growth, but of the epithelial cell types, with a reduced expression of SNAIL and an upregulation of epithelial markers E‐cadherin and Zona occludens‐1 signifying a reduction in EMT . This implies that ALR might indeed have a crucial role to play in the development and progression of HCC.…”
Section: Hepatocellular Carcinoma and Alrmentioning
confidence: 99%
“…These findings seem contradictory, however, evidence suggests that overexpression of sfALR in cancerous HepG2 cells leads to a reduced invasiveness and cell migration. There is still increased cell growth, but of the epithelial cell types, with a reduced expression of SNAIL and an upregulation of epithelial markers E‐cadherin and Zona occludens‐1 signifying a reduction in EMT . This implies that ALR might indeed have a crucial role to play in the development and progression of HCC.…”
Section: Hepatocellular Carcinoma and Alrmentioning
confidence: 99%
“…Previously, it was shown that liver‐specific deletion of ALR resulted in the development of steatohepatitis and hepatocellular carcinoma in mice . ALR was also shown to act as an anti‐metastatic regulator in hepatocellular carcinoma . Although, these studies showed the effect of ALR, there was a paucity of data on the molecular mechanisms of ALR regulating the proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Despite the advance in our understanding of NASHinduced HCC provided by the present study, there are questions that remain unaddressed. Although data for the latter are preliminary owing to the low number of patients examined, a role of reduced ALR expression in steatohepatitis seems to be evident.…”
mentioning
confidence: 88%